488 Pengaruh Electronic Word Of Mouth (E-Wom) Dan Viral Marketing Terhadap Minat Beli Konsumen Pawon Steak Pangkalpinang - Wulandari, Elisa; Sumar; Altin, Darus (Cebong Journal, 2023)
This study aims to identify and analyze studies on EWOM (Electronic Word Of Mouth), Viral Marketing, and buying interest, This research method uses descriptive research. The method used is quantitative method. The number of samples in this study were 96 respondents using a simple random sampling technique. The analysis model used is multiple linear regression analysis. This result showed that the Pawon Steak Pangkalpinang was in the good category. The results of multiple regression analysis testing showed positive result for all existing variables. While the t test and f test show that the EWOM (Electronic Word Of Mouth) and Viral Marketing variables have a positive and significant effect on buying interest in Pawon Steak Pangkalpinang